Nephrotoxicity of calcineurin inhibitors as a risk factor for BK polyomavirus replication after kidney transplantation - Krejčí, Karel; Tichý, Tomáš; Bednaříková, Jana; Bartková, Margita; Žamboch, Kamil; Orság, Jiří; Zadražil, Josef (Journal of medical virology, 2021)
BK polyomavirus-associated nephropathy (PyVAN) is responsible for a significant percentage of transplanted kidneys prematurely terminating their function. Its occurrence is closely related to the intensity of immunosuppressive therapy. In a group of 161 newly transplanted patients, we prospectively evaluated 457 protocol renal biopsies performed within the first year after transplantation. Using the calcineurin inhibitors (CI) nephrotoxicity score, the incidence of nephrotoxicity was monitored as a manifestation of excessive immunosuppression. Findings were correlated with clinical evidence of active BK polyomavirus (BKPyV) replication and PyVAN. Compared to the normal histology, nephrotoxicity was associated with more frequent BKPyV viremia and viruria (p = .01 and p < .01, respectively) and more common occurrence of PyVAN. The persistence of toxicity in the subsequent biopsy proved to be a negative risk factor of viremia and viruria (p = .03 and p < .01, respectively), independently of the initial BKPyV status. Toxicity could also be used as a predictor of viremia and viruria (p = .04 and p < .01, respectively) even in the absence of viral replication at the time of initial biopsy. The early histological manifestation of CI nephrotoxicity was associated with significant BKPyV reactivation in the risky first posttransplant year.
Keywords: Biopsy; Humans; lidé středního věku; nemoci ledvin; Risk Factors; virus BK; Tumor Virus Infections; ledviny; kidney transplantation; Female; rizikové faktory; mladý dospělý; dospělí; Aged; BK Virus; Kidney; protocol biopsy; senioři; lidé; polyomavirové infekce; Viremia; imunosupresivní léčba; Calcineurin Inhibitors; biopsie; Virus Replication; Polyomavirus Infections; Adult; transplantace ledvin; ženské pohlaví; Male; Middle Aged; BK polyomavirus-associated nephropathy; Adolescent; incidence; Incidence; calcineurin inhibitors; Immunosuppression Therapy; replikace viru; Kidney Transplantation; Young Adult; inhibitory kalcineurinu; příjemce transplantátu; Transplant Recipients; viremie; mužské pohlaví; prospektivní studie; Kidney Diseases; nephrotoxicity; mladiství; infekce onkogenními viry; Prospective Studies